(untitled) (Journal of Academic Research, 2026)
In this article, the source rock potential in the oil-bearing areas of the north-eastern parts of Libya is reviewed. The specific areas which are examined are the Cyrenaica Platform, the Ash Shulaydimah Trough and the Al Jabal al Akhdar. The regional Rock Eval geochemical data has been used in conjunction with the well-based Rock Eval data as well as outcomes from exploratory wells to provide information on the Silurian to Paleogene potential source rock distribution and quality. The Paleocene/Eocene source rocks possess excellent quality locally, with hydrogen index values ranging from 700 to 970 mg of HC/g TOC and approximately 1.9 to 8.7 weight % organic carbon. Generally Cretaceous periods show moderate source quality with TOC levels ranging between 0.6 and 2.2wt% and HI levels of 55 to 183 mg HC/g TOC. Locally hydrocarbon generation has been confirmed by well control. This includes a Devonian sandstone gas show which is thought to originate from Silurian shales beneath. Nonetheless, no commercial discoveries have so far been made. Thermal maturity patterns of the source rocks in the area are very varied due to various short-term burial episodes and the area being uplifted after the deposits had been laid down. This occurs specifically in Al Jabal al Akhdar and the Ash Shulaydimah Trough. In the Cyrenaica region, petroleum system effectiveness is limited primarily by small kitchen volumes, restricted migration distances, and reduced hydrocarbon charge, rather than by the absence of organic-rich strata.